blaCTX-M-152, a Novel Variant of CTX-M-group-25, Identified in a Study Performed on the Prevalence of Multidrug Resistance among Natural Inhabitants of River Yamuna, India - Azam, Mudsser; Jan, Arif T.; Haq, Qazi M. R. (Frontiers in Microbiology, 2016)
Natural environment influenced by anthropogenic activities creates selective pressure for acquisition and spread of resistance genes. In this study, we determined the prevalence of Extended Spectrum β-Lactamases producing gram negative bacteria from the River Yamuna, India, and report the identification and characterization of a novel CTX-M gene variant blaCTX-M-152. Of the total 230 non-duplicate isolates obtained from collected water samples, 40 isolates were found positive for ESBL production through Inhibitor-Potentiation Disc Diffusion test. Based on their resistance profile, 3% were found exhibiting pandrug resistance (PDR), 47% extensively drug resistance (XDR) and remaining 50% showing multidrug resistant (MDR). Following screening and antimicrobial profiling, characterization of ESBLs (blaTEM and blaCTX-M) and mercury tolerance determinants (merP, merT and merB) were performed. In addition to abundance of blaTEM-116 (57.5%) and blaCTX-M-15 (37.5%), bacteria were also found to harbour other variants of ESBLs like blaCTX-M-71 (5%), blaCTX-M-3 (7.5%), blaCTX-M-32 (2.5%), blaCTX-M-152 (7.5%), blaCTX-M-55 (2.5%), along with some non-ESBLs; blaTEM-1 (25%) and blaOXY (5%). Additionally, co-occurrence of mercury tolerance genes were observed among 40% of isolates. In silico studies of the new variant, blaCTX-M-152 were conducted through modelling for the generation of structure followed by docking to determine its catalytic profile. CTX-M-152 was found to be an out-member of CTX-M-group-25 due to Q26H, T154A, G89D, P99S and D146G substitutions. Five residues Ser70, Asn132, Ser237, Gly238 and Arg273 were found responsible for positioning of cefotaxime into the active site through seven H-bonds with binding energy of -7.6 Kcal/mol. Despite small active site, co-operative interactions of Ser237 and Arg276 were found actively contributing to its high catalytic efficiency. To the best of our knowledge, this is the first report of blaCTX-M-152 of CTX-M-group-25 from Indian subcontinent. Taking a note of bacteria harbouring such high proportion of multidrug and mercury resistance determinants, their presence in natural water resources employed for human consumption increases the chances of potential risk to human health. Hence, deeper insights into mechanisms pertaining to resistance development are required to frame out strategies to tackle the situation and prevent acquisition and dissemination of resistance determinants so as to combat the escalating burden of infectious diseases.